European enterprises in crisis time - Stefaniak-Kopoboru, Joanna; Kuczewska, Joanna (Managerial Economics, 2014)
The economic crisis it is a rapid economic downturn. National economies are increasingly intertwined through trade and capital what results in fast transmission of the crisis between countries. The crisis results mainly in the deteriorating financial situation of enterprises and in the increase of unemployment, the deterioration in consumer confidence and the reduction of purchases. Under such an unstable macroeconomic environment European companies were forced to review their strategies and maintain a high flexibility for their reactions to changes in the environment. The promotion of competitiveness of European enterprises has become the priority of public regional, national and supranational authorities. Any initiatives hads and still have a great role in building a sustainable and permanent competitive position of the European companies. Companies operating in the European Union are in a unique situation, because they might receive a direct and indirect support to combat the negative effects of the crisis and to enhance their competitiveness on both the national and Community levels. The European companies are offered a wide range of support in the form of the pan-European networks and services, as well as the financial programmes. This results in new opportunities for the effective functioning of European companies and in the improvement of their competitiveness in a difficult period of economic crisis and beyond.